Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s10020-022-00563-9
|View full text |Cite
|
Sign up to set email alerts
|

SIGIRR deficiency contributes to CD4 T cell abnormalities by facilitating the IL1/C/EBPβ/TNF-α signaling axis in rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is a complex autoimmune disease with multiple etiological factors, among which aberrant memory CD4 T cells activation plays a key role in the initiation and perpetuation of the disease. SIGIRR (single immunoglobulin IL-1R-related receptor), a member of the IL-1 receptor (ILR) family, acts as a negative regulator of ILR and Toll-like receptor (TLR) downstream signaling pathways and inflammation. The aim of this study was to investigate the potential roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Plasma cells produce characteristic autoantibodies including rheumatoid factor and anti-cyclic citrullinated peptide [ 31 ]. Activated CD4+ memory T cells produce many cytokines, ultimately leading to joint damage in RA [ 32 ]. Monocytes and macrophages are important components of innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cells produce characteristic autoantibodies including rheumatoid factor and anti-cyclic citrullinated peptide [ 31 ]. Activated CD4+ memory T cells produce many cytokines, ultimately leading to joint damage in RA [ 32 ]. Monocytes and macrophages are important components of innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Argyriou et al [ 165 ] identified 2 peripheral helper T cell states and a cytotoxic CD4 + T cell subset with a common differentiation pathway in the synovial fluid of RA patients at single-cell resolution. Besides, SIGIRR, preferentially expressed by memory CD4 + T cells, could inversely regulate RA disease activity via IL-1/C/EBPβ/TNF-α signaling axis [ 166 ]. It can be concluded that T cells play an essential role in the pathological mechanisms of RA.…”
Section: Various Applications Of Scrna-seq Research In Skeletal Healt...mentioning
confidence: 99%